2015
DOI: 10.53841/bpsecp.2015.32.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Coaching: A universal strategy for supporting and promoting sustainable emotional and behavioural well-being

Abstract: This paper positions Emotion Coaching as a universal strategy for supporting sustainable emotional and behavioural well-being within community and educational contexts. It offers Emotion Coaching as an effective strategy that promotes resiliency skills and locates it within the broader social agenda. The paper will address the key elements of Emotion Coaching which reflect a bio-psycho-social model for universal well-being and are informed by theory and research from neuro-science, interpersonal neurobiology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 54 publications
0
9
0
2
Order By: Relevance
“…Therefore, when child-child communication is observed, it is evident that children are coaching both their own emotions and those of their counterparts. (Gus, Gilbert, & Rose, 2015).…”
Section: Emotion Coachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when child-child communication is observed, it is evident that children are coaching both their own emotions and those of their counterparts. (Gus, Gilbert, & Rose, 2015).…”
Section: Emotion Coachingmentioning
confidence: 99%
“…The positive effects of the emotion coaching approach on a child's well-being are evident in both home and school environments. Studies have shown that emotion coaching, which is used both at home and at school, strengthens the relationship between the child and the adult and supports the child's ability to manage their emotions (Gus, Gilbert, & Rose, 2015;Rose, McGuire-Snieckus, & Gilbert, 2015), helps children recognize their emotions and solves how to deal with these emotions (Wu et al, 2019), and contributes to their social-emotional development (Rose, 2005, Gilbert & Richards, 2015. In addition, positive effects were observed in children's peers (Buckholdt et al, 2016;Gottman & DeClaire, 1997) and sibling relationships (Cindy & Hendriati, 2020;Shortt et al, 2010).…”
Section: Emotion Coaching In School and Home Environmentmentioning
confidence: 99%
“…EC is both a technique and a philosophical approach to emotions (Gus et al, 2015) which was identified in the 1990s from the work of Gottman and Katz, among others, in their work around parenting practices in the US (Gottman et al, 1996). EC comprises two key elements: empathy, and guidance (Rose et al, 2015).…”
Section: What Is Emotion Coaching?mentioning
confidence: 99%
“…It is posited that EC has a positive influence on neurobiological and physiological development by helping to create the nurturing environments and supportive relationships which children and young people need for healthy development (Gus et al, 2015). It is largely informed by attachment theory (Bowlby, 1969) and polyvagal theory (Porges, 2011).…”
Section: What Is Emotion Coaching?mentioning
confidence: 99%
“…Hasil riset sebelumnya menyatakan bahwa penerimaan orang tua membantu anak membentuk hubungan dengan teman sebayanya lebih baik dan menjadi seseorang yang responsif (Gus et al, 2015). Orang tua dianggap sebagai faktor pelindung dan peredam stres bagi remaja.…”
unclassified